2021
DOI: 10.1007/s40744-021-00323-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Laboratory Features and Associated Factors of Lupus Mesenteric Vasculitis

Abstract: Introduction: Lupus mesenteric vasculitis (LMV) is a rare but potentially life-threatening clinical entity in systemic lupus erythematosus (SLE) patients. Objective: The present study was initiated to explore the clinical features and associated factors of LMV in SLE patients. Methods: We conducted a retrospective study on 50 cases of SLE patients with lupus mesenteric vasculitis (LMV) from January 2010 to December 2019 and 89 cases of non-LMV-SLE patients with similar demographic and comorbidities were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…We also found that cSLE with LMV often had decreased complement C3 and C4. There are similar findings in a paper: complement C3 and C4 are lower in LMV patients than in other SLE [ 8 ]. Therefore, clinicians should pay close attention to abdominal symptoms in cSLE.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We also found that cSLE with LMV often had decreased complement C3 and C4. There are similar findings in a paper: complement C3 and C4 are lower in LMV patients than in other SLE [ 8 ]. Therefore, clinicians should pay close attention to abdominal symptoms in cSLE.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, all cSLE with LMV presented with intestinal wall thickening. The main pathological changes are intestinal wall edema and vascular inflammation, so a typical target sign or double loop sign can be presented on enhanced CT. Mesenteric vascular enhancement occurred in 6 cases in our study, presenting as a comb tooth sign, which is also a specific imaging manifestation in LMV [ 8 ]. We had 3 cases with intestinal congestion with liquid–gas level and diagnosed as intestinal obstruction, which improved after glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lee et al 2 reported a significant decrease in white blood cell (WBC) count among patients with LE, which exhibited a strong correlation with the presence of the disease. In contrast, Wang et al 3 observed no significant difference in WBC count between the LE and non-LE groups; however, they did report a notable reduction in lymphocyte count among patients with LE, indicating its potential diagnostic value. The red cell distribution width (RDW), Which is an indicator of chronic inflammation, has been demonstrated as a valuable marker for determining the activity of SLE.…”
Section: Introductionmentioning
confidence: 80%
“…Routine hematological parameters may exhibit alterations during the onset or active phase of the disease, and certain variations among these parameters could potentially serve as indicators for predicting the likelihood of LE onset. For instance, leukopenia 2 or lymphocytopenia 3 may suggest a higher probability of LE occurrence. NLR and PLR are indicators derived from routine blood parameters that offer greater utility in comprehending a patient's systemic inflammatory state due to their ability to integrate two distinct immune pathways.…”
Section: Discussionmentioning
confidence: 99%